ARCHAEOBOTANICAL INVESTIGATIONS AND HUMAN IMPACT AT THE IMPERIAL HARBOUR OF ROME - Giardini, M.; Giraudi, C.; Goiran, J.P.; Masi, A.; Mazzini, I.; Pepe, C.; Sadori, L. (Annali di Botanica, 2013)
Remnants of the ancient harbour of Rome are located in the Tiber delta area 3.5 km away from the present coastline. It was the main Rome maritime port from the middle of the first century to Late Antiquity. In 42 AD, emperor Claudius started the excavation of the harbour. Then, the Emperor Trajan added to the former construction, which had gradually silted up, a hexagonal basin in an inner position. The objective of this multidisciplinary study was to reconstruct the plant cultural landscape in the harbour applying detailed pollen, microcharcoal, and plant macroremains recovered from two cores (PTS5 and PTS13) drilled in the area of the Claudius harbour. The chronological framing of the records is based on stratigraphical criteria, radiocarbon dates, archaeological and historical data. The two cores record different periods of time. One core shows the first phases of the harbour activities, with a plant landscape typical of a coastal environment. The other one records a stronger human impact related to the presence of Portus town and of medieval settlements. Anthropogenic pollen indicators (sensu Behre and Jacomet 1991) as well as strong fire use/occurrence were increasing in the first centuries AD. These results will be completed with new core data from the extant Trajan lake, granting the possibility to study a record spanning the last two millennia.